Investigation of effect of assistive grouser attack angle when moving in unconsolidated soft sand inclination slope using Discrete Element Method (DEM) simulation - Siti Suhaila, Sabarudin; Ahmad Najmuddin, Ibrahim; Yasuhiro, Fukuoka (IEEE, 2020)
Assistive grouser is an alternative grouser purposed by previous researchers that were used to help wheel rover to improve its performance especially when traversing on unconsolidated soft sand inclination slope. When using a normal grouser (conventional grouser), as the wheel rotates, the grouser pushes the sand particles under the wheel upward and toward the back of the wheel, and causing the wheel to get stuck into the sand surface as the wheel starts digging the sand. But by attaching the assistive grouser, it helps to minimize the subsequence sinkage. Assistive grousers are able to adjust its angle of attack when penetrating into the sand slope surface. Assistive grouser produces horizontal traction force that is similar to the bulldozing movement concept. When assistive grouser moves, it enters and exits sand surface without moving a large amount of sand particles from below of the wheel toward the back of the wheel and prevent the wheel from the stuck phase. From the previous experiment, by using assistive grouser with adjustable angle, it helps to improve the performance of wheel rover in term of minimizing the sand movement from under the wheel when the wheel rotates, less sinkage, and less current consumed during the movement of the wheel. However, during the experiment, the interaction between the assistive grouser and the sand cannot be seen clearly. The purpose of this study is to investigate and observe the interaction between assistive grouser (with varying angle of attack) and the sand particles especially on sand surface inclination slope by using computer simulation-Discrete Element Method (DEM) simulation at high slip condition. From the simulation, the effect of adjustable assistive grouser angle toward the traction force generated when the grouser and sand interact was observed. The highest normal force generated by using adjustable assistive grouser with 30-degree angle is around 900 N while the highest normal force generated by assistive grouser 0-degree angle is around 450 N. Assistive grouser that have same angle with the sand surface slope produced higher normal force and lead to produce higher traction force. The traction force helps the rover to climb the surface slope and move forward. And by using assistive grouser 30-degree, the area of destructive area is 230 cm 2 which is bigger compared to assistive grouser 0-degree with 161 cm 2 . Destructive area portrays the relation between the grouser-sand and sand-sand particles.